Nebulised liposomal amphotericin B for Aspergillus lung diseases: case series and literature review. Issue 3 (March 2015) - Godet, Cendrine; Goudet, Véronique; Laurent, François; Moal, Gwenaël Le; Gounant, Valérie; Frat, Jean‐Pierre; cateau, Estelle; Roblot, France; Cadranel, Jacques
Summary Over the past 10 years the incidence of Aspergillus spp. has significantly increased, and it is now the most widespread air transmission fungal pathogen in developed countries. Whatever the clinical expression of the pulmonary disease and despite recent progress in antifungal drug therapy, morbidity and mortality related to aspergillosis lung disease still constitute a serious threat for immunosuppressed or mildly immunocompromised patients. Moreover, the treatments currently used have many limitations due to adverse effects and drug interactions. Finally, subjects exposed to azoles present an increased risk of Aspergillus‐resistant strain emergence. We have reported five cases with aspergillosis lung diseases that were either difficult to control or in which patients had a contra‐indication to triazole therapy, but which showed durable improvement following the administration of nebulised liposomal amphotericin B. Our alternative strategy could be of interest for patients with aspergillosis lung disease who otherwise cannot be conventionally treated by triazoles.